PENGARUH PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PADA PT TASMA PUJA DI PEKANBARU - Agustin Basriani Martina (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2017)
This study, entitled " Effects of Job Promotion To Employees Performance at PT Tasma Pujain Pekanbaru ". The purpose of this study to determine the effect of job promotion toemployess performance at PT Tasma Puja in Pekanbaru.The population in this study were a/1 employees at PT Tasma Puja in Pekanbaru in2015 which amounted to 470 people. Samples in this study using the formula slovin. Methodsof data collection is questionnaire and documentation. Methods of data analysis used in thisresearch are descriptive and quantitative tests included simple linear regression, hypothesistesting with using the t test and the coefficient of determination.The test results of simple linear regression is Y = 0,515 + 0.064 X. And t test results can beseen that the job promotion had significant influence to employees performance at PT TasmaPuja in Pekanbaru. Coefficient of determination was 22.4%, while the rest influenced by othervariables that not examined in this study-Suggestions in this research is PT Tasma Puja needto consider and implement a system of promotion subjectively to employees, so there is nojealousy mnong employees.Keywords: job promotion, employees performance.